Preliminary investigation on rotifer (Brachionus plicatilis) as natural food for polychaete worm (Marphysa iloiloensis): growth, setiger, and survival performance - ROBLES, Rizal Jhunn F.; PEJANA, Delia T.; JANI, Sheyada J.; NIAN, Cherry T.; IMLANI, Ainulyakin H.; ELDANI, Abdurizal A.; SARRI, Jurmin H. (Zenodo, 2023)
{"references": ["Alava, V. R., Bi\u00f1as, J. B., & Mandario, M. A. (2017). Breeding and culture of the polychaete, Marphysa mossambica, as feed for the mud crab in Philippines: In the forefront of the mud crab industry development. Proceedings of the 1st National Mud Crab Congress. Aquaculture Department, Southeast Asian Fisheries Development Center, Iloilo, Philippines, 16-18 November 2015 (pp. 39-45).", "Bautista-Teruel, M. N., Maquirang, J. R. H., Pe\u00f1a, M. D., & Balinas, V. T. (2016). Test of refined formulated feed for the grow-out culture of tropical abalone Haliotis asinina (Linnaeus 1758) in concrete land-based tanks. Journal of Shellfish Research, 35(3), 633-639. https://doi.org/10.2983/035.035.0309", "Bischoff, A. A., Fink, P., & Waller, U. (2009). The fatty acid composition of Nereis diversicolor cultured in an integrated recirculated system: possible implications for aquaculture. Aquaculture, 296(3-4), 271-276. https://doi.org/10.1016/j.aquaculture.2009.09.002", "Brummett, R. (2008). Role of aquaculture in increasing water productivity (Report No. 4). Challenge Program on Water and Food\u2013Aquatic Ecosystems and Fisheries Review Series. http://marineagronomy.org/sites/default/files/Role%20of%20Aquaculture%20in%20Increasing%20Water%20Productivity.pdf", "Budaeva, N., & Fauchald, K. (2011). Phylogeny of the Diopatra generic complex with a revision of Paradiopatra Ehlres, 1887 (Polychaeta: Onuphidae). Zoological Journal of the Linnean Society, 163(2), 319-436. https://doi.org/10.1111/j.1096-3642.2011.00701.x", "Cabral, S., Alves, A. S., Castro, N., Chainho, P., S\u00e1, E., da Fonseca, L. C., ... & Costa, J. L. (2019). Polychaete annelids as live bait in Portugal: Harvesting activity in brackish water systems. Ocean & Coastal Management, 181, 104890. https://doi.org/10.1016/j.ocecoaman.2019.104890", "Cole, V. J., Chick, R. C., & Hutchings, P. A. (2018). A review of global fisheries for polychaete worms as a resource for recreational fishers: diversity, sustainability and research needs. Reviews in Fish Biology and Fisheries, 28(3), 543-565. https://doi.org/10.1007/s11160-018-9523-4", "Costa, P. F. E., Gil, J., Passos, A. M., Pereira, P., Melo, P., Batista, F., & Fonseca, L. C. D. (2006). The market features of imported non-indigenous polychaetes in Portugal and consequent ecological concerns. Scientia Marina, 70S3, 287-292. https://doi.org/10.3989/scimar.2006.70s3287", "Cunha, T., Hall, A., & Queiroga, H. (2005). Estimation of the Diopatra neapolitana annual harvest resulting from digging activity in Canal de Mira, Ria de Aveiro. Fisheries research, 76(1), 56-66. https://doi.org/10.1016/j.fishres.2005.05.008", "Desrina, J. V., Verdegem, M. C. J., & Vlak, J. M. (2018). Polychaetes as potential risks for shrimp Pathogen transmission. Asian Fisheries Science S, 31, 155-167.", "Du Clos, K. T. (2012). Polychaete Burrowing Behavior in Sand and Mud. (Publication No. 1872) [Master of Science Thesis, University of Maine]. http://digitalcommons.library.umaine.edu/etd/1872", "Evans, M. (2019). Catching fish to feed fish: Report details 'unsustainable'fishmeal and oil industry. (4 December 2019) Mongabay News & Inspirations from Nature's Frontline. https://news.mongabay.com/2019/12/catching-fish-to-feed-fish-report-details-unsustainable-fishmeal-and-oil-industry/", "Fauchald, K. (1977). The polychaete worms. Definitions and keys to the orders, families and genera. Natural History Museum of Los Angeles County, Science Series. https://repository.si.edu/handle/10088/3435", "Fauchald, K., & Jumars, P. A. (1979). The diet of worms: a study of polychaete feeding guilds. Oceanography and marine Biology annual review. https://repository.si.edu/handle/10088/3422", "Gambi, M. C., Castelli, A., Giangrande, A., Lanera, P., Prevedelli, D., & Zunarelli Vandini, R. (1994, July). Polychaetes of commercial and applied interest in Italy: an overview. [Conference presentation]. Actes de la 4eme Conference internationale des Polychetes. Memoires du Museum National d'Histoire Naturelle de Paris (Vol. 162, pp. 593-601). https://www.researchgate.net/publication/291783235_Polychaetes_of_commercial_and_applied_interest_in_Italy_An_overview", "Garc\u00eas, J. P., & Pereira, J. (2011). Effect of salinity on survival and growth of Marphysa sanguinea Montagu (1813) juveniles. Aquaculture international, 19(3), 523-530. https://doi.org/10.1007/s10499-010-9368-x", "Garc\u00eda-Alonso, J., M\u00fcller, C. T., & Hardege, J. D. (2008). Influence of food regimes and seasonality on fatty acid composition in the ragworm. Aquatic Biology, 4(1), 7-13. https://doi.org/10.3354/ab00090", "Jumars, P. A., Dorgan, K. M., & Lindsay, S. M. (2015). Diet of worms emended: an update of polychaete feeding guilds. Annual review of marine science, 7(1), 497-520. https://doi.org/10.1146/annurev-marine-010814-020007", "Kihia, C. M., Waigwa, S. W., & Munyaka, J. M. (2017). Polychaete (Maphysa mosambica) morphometrics and their use in estimation of polychaete size and breeding values of bait exploited by artisanal fishers at the Kenyan coastline. Advances in Ecological and Environmental Research, 1-13.", "Thi Thu, E. V., Rahman, M., Phoo, W. W., & Kim, C. H. (2019). Salinity effects on growth and survival of the polychaete Rockworm Marphysa sanguinea (Montagu, 1813) juveniles and adults. Journal of Aquaculture Research and Development, 10, 560. https://doi.org/10.4172/2155- 9546.1000562", "Kim, K. H., Kim, B. K., Kim, S. K., Phoo, W. W., Maran, V., & Kim, C. H. (2017). Appropriate feeding for early juvenile stages of eunicid polychaete Marphysa sanguinea. Fisheries and Aquatic Sciences, 20(1), 1-9. https://doi.org/10.1186/s41240-017-0064-x", "Lim, J. A., Loo, P. L., Tan, K. S., & Ng, N. K. (2021). Fish culture waste improves growth and fatty acid composition of the polychaete Namalycastis sp.(Nereididae) and its potential use as feed for mud crabs. Aquaculture Research, 52(6), 2622-2639. https://doi.org/10.1111/are.15109", "Limsuwatthanathamrong, M., Sooksai, S., Chunhabundit, S., Noitung, S., Ngamrojanavanich, N., & Petsom, A. (2012). Fatty acid profile and lipid composition of farm-raised and wild-caught sandworms, Perinereis nuntia, the diet for marine shrimp broodstock. Asian Journal of Animal Sciences, 6(2), 65-75. https://doi.org/10.3923/ajas.2012.65.75", "Mandario, M. A. E. (2020). Survival, growth and biomass of mud polychaete Marphysa iloiloensis (Annelida: Eunicidae) under different culture techniques. Aquaculture Research, 51(7), 3037-3049. https://doi.org/10.1111/are.14649", "Mandario, M. A. E., Alava, V. R., & A\u00f1asco, N. C. (2019). Evaluation of the bioremediation potential of mud polychaete Marphysa sp. in aquaculture pond sediments. Environmental Science and Pollution Research, 26(29), 29810-29821. https://doi.org/10.1007/s11356-019-06092-z", "Mandario, M. A. E., Castor, N. J. T., & Balinas, V. T. (2022). Effects of feeding rate and sediment depth on the survival, growth performance, and biomass of mud polychaete Marphysa iloiloensis from early juvenile to adult in grow-out tanks. Aquaculture, 548, 737731. https://doi.org/10.1016/j.aquaculture.2021.737731", "Meunpol, O., Duangjai, E., Yoonpun, R., & Piyatiratitivorakul, S. (2010). Detection of prostaglandin E2 in polychaete Perinereis sp. and its effect on Penaeus monodon oocyte development in vitro. Fisheries Science, 76(2), 281-286. https://doi.org/10.1007/s12562-009-0208-8", "Meunpol, O., Iam-Pai, S., Suthikrai, W., & Piyatiratitivorakul, S. (2007). Identification of progesterone and 17\u03b1-hydroxyprogesterone in polychaetes (Perinereis sp.) and the effects of hormone extracts on penaeid oocyte development in vitro. Aquaculture, 270(1-4), 485-492. https://doi.org/10.1016/j.aquaculture.2007.05.031", "Meunpol, O., Meejing, P., & Piyatiratitivorakul, S. (2005). Maturation diet based on fatty acid content for male Penaeus monodon (Fabricius) broodstock. Aquaculture Research, 36(12), 1216-1225. https://doi.org/10.1111/j.1365-2109.2005.01342.x", "Naessens, E., Lavens, P., Gomez, L., Browdy, C. L., McGovern-Hopkins, K., Spencer, A. W., ... & Sorgeloos, P. (1997). Maturation performance of Penaeus vannamei co-fed Artemia biomass preparations. Aquaculture, 155(1-4), 87-101. https://doi.org/10.1016/S0044-8486(97)00111-7", "Nguyen, B. T., Koshio, S., Sakiyama, K., Ishikawa, M., Yokoyama, S., & Kader, M. A. (2012). Effects of polychaete extracts on reproductive performance of kuruma shrimp, Marsupenaeus japonicus Bate\u2013Part II. Ovarian maturation and tissue lipid compositions. Aquaculture, 334, 65-72. https://doi.org/10.1016/j.aquaculture.2011.11.038", "Olive, P. J. (1999). Polychaete aquaculture and polychaete science: a mutual synergism. Hydrobiologia, 402, 175-183. https://doi.org/10.1023/A:1003744610012", "Olive, P. W. (1994). Polychaeta as a world resource: a review of patterns of exploitation as sea angling baits and the potential for aquaculture based production. M\u00e9moires du Mus\u00e9um national d'histoire naturelle (1993), 162, 603-610.", "Palmer, P. J. (2010). Polychaete-assisted sand filters. Aquaculture, 306(1-4), 369-377. https://doi.org/10.1016/j.aquaculture.2010.06.011", "Palmer, P. J., Wang, S., Houlihan, A., & Brock, I. (2014). Nutritional status of a nereidid polychaete cultured in sand filters of mariculture wastewater. Aquaculture nutrition, 20(6), 675-691. https://doi.org/10.1111/anu.12129", "Panakorn, S. (2015). Polychaetes for shrimp broodstock maturation. Aqua Culture Asia Pacific Magazine, 11(4), 6-11.", "Parry, L., Tanner, A., & Vinther, J. (2014). The origin of annelids. Palaeontology, 57(6), 1091-1103. https://doi.org/10.1111/pala.12129", "Pires, A., Gentil, F., Quintino, V., & Rodrigues, A. M. (2012). Reproductive biology of Diopatra neapolitana (Annelida, Onuphidae), an exploited natural resource in Ria de Aveiro (Northwestern Portugal). Marine Ecology, 33(1), 56-65. https://doi.org/10.1111/j.1439-0485.2011.00463.x", "Pombo, A., Baptista, T., Granada, L., Ferreira, S. M., Gon\u00e7alves, S. C., Anjos, C., ... & Costa, J. L. (2020). Insight into aquaculture's potential of marine annelid worms and ecological concerns: a review. Reviews in Aquaculture, 12(1), 107-121. https://doi.org/10.1111/raq.12307", "Purschke, G., Bleidorn, C., & Struck, T. (2014). Systematics, evolution and phylogeny of Annelida\u2013a morphological perspective. Mem Museum Victoria, 71, 247-269. http://doi.org/10.24199/j.mmv.2014.71.19", "Ricker, W. E. (1979). Growth rates and models. Fish physiology, 677-744. http://doi.org/10.1016/S1546-5098(08)60034-5", "Rouse, G. W., & Fauchald, K. (1998). Recent views on the status, delineation, and classification of the Annelida. American Zoologist, 38(6), 953-964.", "Scaps, P. (2003). The exploitation and aquaculture of marine polychaetes. Bulletin-Societe Zoologique De France, 128(1/2), 21-34.", "Sypitkowski, E., Bohlen, C., & Ambrose Jr, W. G. (2010). Estimating the frequency and extent of bloodworm digging in Maine from aerial photography. Fisheries Research, 101(1-2), 87-93.", "Vijayan, K. K., Raj, V. S., Balasubramanian, C. P., Alavandi, S. V., Sekhar, V. T., & Santiago, T. C. (2005). Polychaete worms - a vector for white spot syndrome virus (WSSV). Diseases of Aquatic Organisms, 63(2-3), 107-111. http://doi.org/10.3354/dao063107", "Watson, G. J., Murray, J. M., Schaefer, M., & Bonner, A. (2017). Bait worms: a valuable and important fishery with implications for fisheries and conservation management. Fish and fisheries, 18(2), 374-388. https://doi.org/10.1111/faf.12178", "Wouters, R., Lavens, P., Nieto, J., & Sorgeloos, P. (2001). Penaeid shrimp broodstock nutrition: an updated review on research and development. Aquaculture, 202(1-2), 1-21. https://doi.org/10.1016/S0044-8486(01)00570-1", "Zanol, J., Fauchald, K., & Paiva, P. C. (2007). A phylogenetic analysis of the genus Eunice (Eunicidae, polychaete, Annelida). Zoological Journal of the Linnean Society, 150(2), 413-434. https://doi.org/10.1111/j.1096-3642.2007.00302.x"]}

Polychaete Marphysa iloiloensis is one of the most common live bait species targeted by bait diggers in Tawi-Tawi, Philippines. It is considered a nutritious and high-protein source of food for aquaculture, either in fresh form or incorporated in feeds. However, as wild populations of polychaete are subject to ecological and animal welfare concerns, along with resource depletion, the literature on feeding polychaete M. iloiloensis larvae is inadequate and scarce, making polychaete aquaculture an ideal alternative. The present study aimed to investigate the rotifer (Brachionus plicatilis) as natural food for the cultured polychaete M. iloiloensis on the growth, setigers, and survival performance. Polychaete M. iloiloensis larvae were fed with three different concentrations of rotifer, namely, Treatment 1 (T1) = 5 mL, Treatment 2 (T2) = 10 mL, and Treatment 3 (T3) = 15 mL cultured for 45 days. Results showed that 5 mL and 10 mL of rotifer stimulated improvement in growth and an increase in setiger count after 45 days of the culture period, although the differences were not significant (p>0.05) compared to 15 mL concentration of rotifer. Moreover, a 5 mL and 10 mL concentration of rotifer significantly increased (p<0.05) polychaete M. iloiloensis survival compared to a 15 mL concentration. Hence, this study suggests that rotifer (B. plicatilis) can effectively alter the diet of the polychaete M. iloiloensis to promote growth, setiger formation segments, and enhance survival.
Keywords: growth; Brachionus plicatilis; setigers; survival; polychaete; Marphysa iloiloensis; 9. Industry and infrastructure; 14. Life underwater